High-school Students' Informal Reasoning and Argumentation about Biotechnology: An indicator of scientific literacy? - Dawson, Vaille; Venville, G. (Routledge, 2009)
The aim of this research was to explore Australian high‐school students’ argumentation and informal reasoning about biotechnology. Data were obtained from semi‐structured interviews with 10 Year‐8 students (12–13 years old), 14 Year‐10 students (14–15 years old) and 6 Year‐12 students (16–17 years old) from six metropolitan high schools in Perth, Western Australia. The transcripts were analysed using both Toulmin’s argumentation pattern and informal reasoning patterns (rational, emotive, and intuitive) as frameworks. The notion of scientific literacy was used as the basis of the theoretical framework to examine the data. Most students used no data or only simple data to justify their claims. Students of all year groups used intuitive and emotive informal reasoning more frequently than rational. Rational informal reasoning was associated with more sophisticated arguments.